Certain Death: Mike Flanagan’s Gothic Antidote to Traumatic Memory and Other Enlightenment Hang-Overs in Doctor Sleep - Erik Bond (Humanities)
This article uses the English Gothic’s eighteenth-century dismantling of male lineage and Enlightenment certainty in Horace Walpole’s The Castle Otranto as a lens for understanding the twenty-first-century commercial popularity of director Mike Flanagan’s Gothic films, particularly Doctor Sleep. Building on Stephen King’s 2013 novel and Stanley Kubrick’s 1980 film The Shining, Flanagan’s Doctor Sleep establishes a new lineage of male writers who value how the Gothic traditions of irrational emotion and doubt can inspire new realms of knowledge to lessen psychological suffering caused by traumatic lineage. By “traumatic lineage” I mean the threat and violence some find necessary to maintain the patrilineal claim that it is “naturally” the only way to organize society. Like Walpole’s mythopoeic Gothic novel, Flanagan’s Gothic films demonstrate how patrilineal lineage damages other men, not just women; thus, Flanagan’s films offer psychological workbooks for practicing a type of reparative masculinity that involves exposure-exercises of cognitive behavior therapy (Doctor Sleep’s “boxing” intrusive, traumatic memories), male communities of care, and interdependent empathy. I support this argument by closely reading how Flanagan’s filmic tools of domestic metaphor, uncanny casting, and repurposed sets from Kubrick’s The Shining not only tell how to exorcise the inherited stills of the Overlook Hotel but also show viewers how to do so. We experience Dan Torrance’s reparative masculinity in real-time, communally sharing and recasting Dan’s horrific images of 40 years ago, but we now relate to them in psychologically helpful ways that enable community. In this way, I illustrate and encourage future study of how Gothic texts not only point to marginalized, repressed problems, but more importantly, how they help us relate differently to a traumatic past and innovate strategies for immediate relief from inherited suffering.